2005
DOI: 10.1051/rnd:2005037
|View full text |Cite
|
Sign up to set email alerts
|

Dose effect of alpha-linolenic acid on lipid metabolism in the hamster

Abstract: -In order to meet dietary requirements, the consumption of α-linolenic acid (ALA, 18:3 n-3) must be promoted. However, its effects on triglyceride (TG) and cholesterol metabolism are still controversial, and may be dose-dependent. The effects of increasing dietary ALA intakes (1%, 10%, 20% and 40% of total FA) were investigated in male hamsters. ALA replaced oleic acid while linoleic and saturated FA were kept constant. Triglyceridemia decreased by 45% in response to 10% dietary ALA and was not affected by hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 55 publications
1
11
0
2
Order By: Relevance
“…Indeed, EPA, DPA or DHA represents less than 0.8% of total FA in our study, even in the group with the highest ALA intake, and could explain the absence of impact on the adipose tissue development of the 21-day old guinea pigs. Previous studies have indicated that n-3 LC-PUFAs enriched diets diminish the hepatic enzymatic activities of endogenous fatty acids synthesis [30] associated with a decrease in plasma TG [31,32]. In the present study, the high ALA intake induced a 2-fold reduction of fractional DNL in the liver at d21 with no impact on total plasma TG concentration.…”
Section: Discussionsupporting
confidence: 54%
“…Indeed, EPA, DPA or DHA represents less than 0.8% of total FA in our study, even in the group with the highest ALA intake, and could explain the absence of impact on the adipose tissue development of the 21-day old guinea pigs. Previous studies have indicated that n-3 LC-PUFAs enriched diets diminish the hepatic enzymatic activities of endogenous fatty acids synthesis [30] associated with a decrease in plasma TG [31,32]. In the present study, the high ALA intake induced a 2-fold reduction of fractional DNL in the liver at d21 with no impact on total plasma TG concentration.…”
Section: Discussionsupporting
confidence: 54%
“…Further, RBO and linseed oil blend significantly decreased serum TG in rats (Chopra & Sambaiah, 2009). The reduction in serum TG in response to feeding of GCO and GCO blended oil could be attributed to decreased activity of fatty acid synthase (FAS), acetyl CoA carboxylase and malic enzyme by ALA reported earlier in rats and hamsters (Morise et al, 2005;Mush, Ojakian, & Williams, 1974).…”
Section: Discussionmentioning
confidence: 79%
“…Indeed, in man, dietary ALA intake was associated with: (1) bioconversion into 20 : 5n-3, which improves the balance of eicosanoids derived from 20 : 5 fatty acids (Pawlosky et al 2001); (2) decreased triglyceridaemia in some patients exhibiting CVD risk factors (Wilkinson et al 2005) or in an epidemiological survey (Djousse et al 2003); and (3) protective effect on the relative risk from fatal CHD (Ascherio et al 1996;Hu et al 1997). Besides, in the male hamster, dietary ALA has been shown to reduce hepatic lipogenesis and triglyceridaemia (Morise et al 2005). The aim of the study was to determine (1) whether the lipoprotein profile and the lipid risk factors of metabolic syndrome and CVD were influenced by fatty acids to the same extent in females as in males, and (2) which were the key enzymes and compartments of lipid metabolism, and the major transcription factors involved in the regulation of lipid metabolism by dietary fatty acids, that are involved in the gender-related differences.…”
Section: A-linolenic Acid: Gender: Lipid Metabolism: Dietary Fatty Acidsmentioning
confidence: 99%